Memetizing and mediatizing: memes as an evangelical discursive strategy - Regiani, Herivelton and Borelli, Viviane (ESSACHESS - Journal for Communication Studies, 2017)
This study addresses a communicational approach to internet memes, understanding them as devices that take place in the process of mediatization of society. It focuses on the discursive aspects involved in the production and reproduction of memes, which are re-signified through operations that involve deframing and reframing and that trigger interdiscursivity. This research analyzes the use of internet memes in the Brazilian Protestant religious field, in web pages that describe themselves as having an evangelical humor. The main objective is to identify the discursive strategies and the effects of meaning constructed through memes. A multiple case study is undertaken, analyzing memes in three web pages chosen from the identification of reading contracts that hold similarities and also singularities, memes that act as enunciation devices by which new interactions of the religious and media fields in the environment of social networks are delineated.
https://katalog.adlr.link/Record/ai-53-701857